Occurrence of aflatoxin M1 in urine samples, milk and dairy products and their associated factors among residents in Terengganu, Malaysia - Ahmad, Farah Nadira (2016)
Nowadays, in conjunction with dramatic growth of population, food safety matter is of concern. The exposure of fungi producing toxin named mycotoxins is one example of food contamination. Aflatoxin M1 (AFM1) is a major metabolite of aflatoxin B1 (AFB1) which is one of many naturally occurring mycotoxins. This cross-sectional comparative population (n=206) based study was comprised of two parts. The first part was to study the associations between socio-demographic, socioeconomic statuses, the consumption of milk and dairy products and the level of awareness, knowledge, attitude and practice on aflatoxin with the occurrence of AFM1 in urine sample among residents in Terengganu. The second part was to screen the occurrence of AFM1 in commonly consumed milk and dairy products and to determine the relationship between the ingestion of AFM1 through milk and dairy products with the level of urinary AFM1. A set of questionnaire and a urine container were provided to each subject. Data collection was carried out from August 2013 to December 2013. The selection of subject and collection of milk products were based on systematic and purposive sampling respectively. The competitive enzyme-linked immunosorbent assay (ELISA) method was used to determine the level of AFM1 in the samples of urine and milk products. Data was analyzed by using SPSS Software version 22.0 Bivariate analyses for the first part observed that urban and female subject were more aware, older and female subjects were more knowledgeable, urban and nonemployed subjects had more attitude, rural, high educated, non-employed and subjects received monthly income RM1500 and above were practiced more toward aflatoxin matter. Besides, urban, high educated subjects and subjects with high knowledge and attitude tend to consume high amount of milk and dairy products. In the other hand, subjects below 30 years old and married subjects were observed to be more at risk to be exposed with AFM1. In term of AFM1 level, subjects below 30 years old, Chinese and non-employed subjects were exposed with higher level of AFM1. This study also found significant associations between milk and dairy products intake and the occurrence of urinary AFM1. For the second part of the study, AFM1 was detected in 39.6% of milk and dairy products tested. The level of contamination ranged from 0.9 to 119.1 ng/L. It was observable that 4 samples were above the European Commission limit and all of them were still below the Malaysian Food Regulation 1985 limit. All in all, both urban and rural subjects in Terengganu were slightly exposed with AFM1 whereas for milk and dairy products commonly consumed by the residents in Terengganu, the exposure of AFM1 was moderate. This study provided a pioneering data on the occurrence of AFM1 in milk and dairy products in Malaysia.